EVALUASI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI JAGUNG (Zea mays L.) DI KECAMATAN SOKARAJA KABUPATEN BANYUMAS - Agus Suprapto (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2013)
This study aimed to evaluate the use of factors of production on corn products, and to determine the use of a combination of production factors that achieved maximum benefit level of the average number of products was produced. The method used in this study is the survey method, and the method of sampling is simple random sampling. The results of the analysis using the Cobb Douglas production function shows that the factors of production acreage and labor significantly and positively to the product of corn, fertilizer production factors significantly and negatively. Seed and pesticide production factors did not significantly affect the product at 95% confidence level. Based on the analysis of the efficiency of utilization of factors of production, it is known that the use of arable land, fertilizer, and labor has not been at its optimal level. The use of factors of production acreage ( X1 ), fertilizer ( X3 ), and labor ( X5 ) in the study area would provide maximum benefit when combined with comparisons X1 : X3 : X5 = 0.0027 : 1 : 0.2757.To produce an average of 14.3243 quintal in the area of research, the combination of X1, X3, and X5 with minimal costs would be achieved if the use of arable land ( X1 ) 0.2689 hectares, fertilizer ( X3 ) 99.76 kilograms, and labor ( X5 ) 27.50 days working men . Key words: evaluation, factors of production, corn.